Preparation of a cattle bone collagen peptide–calcium chelate by the ultrasound method and its structural characterization, stability analysis, and bioactivity on MC3T3-E1 cells. Issue 2 (21st December 2022) - Zhang, Hongru; Qi, Liwei; Wang, Xiaodan; Guo, Yujie; Liu, Jiqian; Xu, Yang; Liu, Chengjiang; Zhang, Chunhui; Richel, Aurore
Abstract : A collagen peptide–calcium chelate was prepared by the ultrasound method for boosting the osteoblast activity. Abstract : This study was designed to prepare a cattle bone-derived collagen peptide–calcium chelate by the ultrasound method (CP–Ca-US), and its structure, stability, and bioactivity on MC3T3-E1 cells were characterized. Single-factor experiments optimized the preparation conditions: ultrasound power 90 W, ultrasound time 40 min, CaCl2 /peptides ratio 1/2, pH 7. Under these conditions, the calcium-chelating ability reached 39.48 μg mg −1 . The result of Fourier transform-infrared spectroscopy indicated that carboxyl oxygen and amino nitrogen atoms were chelation sites. Morphological analysis indicated that CP–Ca-US was characterized by a porous surface and large particles. Stability analysis demonstrated that CP–Ca-US was stable in the thermal environment and under intestinal digestion. CP–Ca-US showed more stability in gastric juice than the chelate prepared by the hydrothermal method. Cell experiments indicated that CP–Ca-US increased osteoblast proliferation (proliferation rate 153% at a concentration of 300 μg mL −1 ) and altered the cell cycle. Significantly, CP–Ca-US enhanced calcium absorption by interacting with calcium-sensing receptors and promoted the mineralization of MC3T3-E1 cells. This study provides the scientific basis for applying the ultrasound method to prepare peptide–calcium chelates and clarifies the positive role of chelates in bone building.